Anomalous microwave heating effects in Ce-doped La(0.7)Sr(0.3)MnO(3): possible role of grain boundary capacitative effects across cerium solubility limit - Kale, Sangeeta N.; Mona, J.; Lofland, S. E.; Kulkarni, S. D.; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
Ce-doped manganite bulk nanocompacts [La(0.7-x)Ce(x)Sr(0.3)MnO(3) (0 < x < 0.1)] are studied for their microwave heating properties at 2.45 GHz. The heating effect is found to be nonmonotonic as a function of cerium concentration, and anomalously large heating (burning) is observed for a small concentration window near x=0.03. The x-ray diffraction studies show signatures of CeO(2) phase in x>0.03 samples. The various characterizations collectively point to the key role of the developing grain boundary CeO(2) layer which leads to highest capacitative intergrain-coupling and related charging-discharging effects when it is thinnest near the apparent Ce solubility limit of x similar to 0.03. (c) 2008 American Institute of Physics.